2021
DOI: 10.1186/s13075-021-02624-6
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory impairment in patients with primary Sjogren’s syndrome and its correlation with organ involvement and immunological abnormalities

Abstract: Objective Patients with autoimmune diseases often present with olfactory impairment. The aim of the study was to assess the olfactory functions of patients with primary Sjögren’s syndrome and to correlate these findings with their disease activity. Methods Fifty-two patients with primary SS and 52 sex- and age-matched healthy control subjects were included. All of them underwent clinical and laboratory examination. Olfactory functions were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…In addition to general taste perception, some studies revealed various degrees of dysfunction for the main types of taste in SS patients. Sweet taste was the least affected, while bitter was the most impaired in the SS group [12]. Similar results were obtained by Kamel et al, who reported that within the SS group, the threshold for sweet taste was much less affected than the threshold for sour, salty and bitter [6].…”
Section: Types Of Chemosensory Dysfunctions In Ss and Their Severitysupporting
confidence: 85%
See 2 more Smart Citations
“…In addition to general taste perception, some studies revealed various degrees of dysfunction for the main types of taste in SS patients. Sweet taste was the least affected, while bitter was the most impaired in the SS group [12]. Similar results were obtained by Kamel et al, who reported that within the SS group, the threshold for sweet taste was much less affected than the threshold for sour, salty and bitter [6].…”
Section: Types Of Chemosensory Dysfunctions In Ss and Their Severitysupporting
confidence: 85%
“…In the SS group, the self-reported taste and smell scores on VAS were significantly lower than those of healthy controls [1]. Ageusia, hypogeusia, anosmia, and hyposmia were more frequent in the SS group than in healthy people [1,12]. Although the main types of taste and smell disorders were hyposmia and hypogeusia, anosmia, and ageusia were relatively common in the SS group [1].…”
Section: Types Of Chemosensory Dysfunctions In Ss and Their Severitymentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, Xu et al recently shown in a study including 52 pSS patients versus matched healthy control subjects, impaired olfactory functions (assessed by odors threshold, identification, and memory tests) in pSS patients (all p ≤ 0.01); they found more anosmia and hyposmia in pSS patients. They also highlight a close correlation between olfactory dysfunction and pSS severity or activity (evaluated by ESSDAI and ESSPRI scores) and immunological abnormalities (Table 2 ) [ 4 ]. However, we have not identified any specific longitudinal studies on olfactory disorders in SS patients, to further strengthen these results.…”
Section: Discussionmentioning
confidence: 99%
“…Today, chemosensory dysfunction remains rarely investigated during the medical follow-up of patients although the recent COVID-19 pandemic reveal that it could be a strong and clear sign of systemic condition [ 2 , 3 ]. Chemosensory dysfunction has been seldom reported in primary Sjögren’s syndrome (pSS) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%